Analyzing the differences: U-dictionary and google translate's English-to-Indonesian speech translation - Suhartawan Budianto; Devito Andharu; Ratna Kartini (Universitas Muhammadiyah Malang, 2024)
This study investigated the use of U-Dictionary and Google Translate in translating English Speech into the Indonesian language. This study aimed to test whether U-Dictionary outperforms Google Translate in translating English Speech into Indonesian. The true experimental design was applied to examine the result of the translation from U-Dictionary and Google Translate. Two raters assessed the translation result from U-Dictionary and Google Translate using a translation scoring rubric (In the